New peritoneal dialysates, for which benefits ? - François Vrtovsnik (RDPLF, 2018)
The ideal peritoneal dialysis solution should allow efficient withdrawal of waste products of the metabolism and water and solutes equilibrium with minimal side effects for the patient and the peritoneal membrane. Glucose degradation products (GDP) resulting from the manufacturing process play a major toxic role and new biocompatible PD solutions with low GDP content and a more physiological bicarbonate or bicarbonate/lactate buffer have brought a clear benefit in experimental studies; however, in clinical cohorts and meta-analysis, the benefits of these solutions appear limited to better preservation of residual renal function and of diuresis. Glucose is the principal osmotic agent although hypertonic glucose solutions have a deleterious effect on PD, and their use should be restrained. Dialysate concentrations of sodium, calcium and magnesium are close to plasma; their diffusive transport is thus limited and their net peritoneal transport mainly depends on the ultrafiltration volume. A dialysate calcium concentration above 1.25 mmol/l generates a calcium load which may contribute to the high prevalence of adynamic bone disease in PD patients; this should be avoided. Low sodium dialysis solutions experimentally improve sodium diffusive transport and extraction in PD patients; the clinical benefit of this approach has to be confirmed.